Democracy Amid Pandemic: A Survey Experiment on How Covid‐19 Affectedness Influences Support for Anti‐Liberal Policies - Annika Werner; Reinhard Heinisch (Politics and Governance)
Do people support ostensibly effective policy measures that curtail liberal rights and civil liberties or instead stick to liberal principles when confronted with an unprecedented crisis? This article examines the relationship between individuals’ perceptions of the Covid-19 pandemic and their attitudes toward democracy as they consider effective countermeasures. It asks (a) whether individuals’ sense of being affected by the pandemic shapes their attitudes toward democratic policymaking and (b) whether this relationship is moderated by trust and authoritarianism. The analysis builds on a customized survey in Austria that includes a conjoint experiment to test the acceptability of various illiberal policies. It shows that while feeling affected by Covid-19 does not have the hypothesized effect, there are strong interactions with respondents’ political attitudes. Citizens’ willingness to sacrifice democracy for more effective policies depends both on whether they perceive the pandemic as a personal problem and on their attitudes toward government and democracy.